Kitosan dari Limbah Kulit Kepiting Rajungan (Portunus sanginolentus L.) sebagai Adsorben Zat Warna Biru Metilena - Tanasale, Matheis F.J.D.P.; Killay, Amos; Laratmase, Marsela S (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2012)
The chitosan from shell of crabs (Portunus sanginolentus L.) waste was produced from deproteinization, demineralization, depigmentation,and deacetylation steps. This process was obtained 22.66% chitosan which identified by FTIR spectrophotometry and had 65.47% degree ofdeacetylation. This chitosan was used to adsorb methylene blue dye which fit to the Langmuir isotherm with 0.0312 l mg -1 equilibriumconstant of adsorption (K) and 4.20 mg g -1 maximum capacity of adsorption (q m).